Posterior Sinuplasty: A New Strategy for Managing Hydrocolpos in Cloaca—Case Series - AbouZeid, Amr AbdelHamid; Abdelmoniem, Ahmed Saad; Fathy, Mohamed Abdelrahman; Negm, Mohamed Ahmed; Mohammad, Shaimaa Abdelsattar (European Journal of Pediatric Surgery Reports, 2024)
We present a simple surgical technique aiming to improve urine outflow through the common urogenital sinus in cloaca and facilitate drainage of existing hydrocolpos. The study included three cases of cloaca with associated hydrocolpos that were operated during the period 2022 through 2023. The patient is placed in the prone position for a standard posterior sagittal anorectoplasty. The distal rectal fistula is severed flush with the vagina/sinus leaving an open defect in the posterior wall of the vagina/sinus. The defect is then widened distally via a vertical incision (∼1 cm) through the posterior wall of the common urogenital sinus toward but not reaching the perineum. This vertical defect is then closed horizontally displacing the posterior vaginal wall downwards toward the perineum (posterior sinuplasty). The postoperative recovery was uneventful in the three cases. Adequate drainage of hydrocolpos was confirmed by imaging at follow-up, as well as improvement of upper urinary tract dilatation. In selected cases of cloaca, posterior sinuplasty is a simple procedure that can be applied during anorectoplasty to provide effective drainage of associated hydrocolpos.
Keywords: anorectal malformations; urogenital sinus; vaginal septum; Mullerian anomalies; congenital